Investigating the role of professional disruption in Chinese journalists' embrace of public relations: a social identity perspective. Issue 1 (2nd January 2022) - Qiu, Hongfeng; Lou, Chen
Abstract: This study investigates whether the declining economic performance and social status of traditional news media, which are two dimensions indicating the professional disruption of journalism, are associated with journalists' engagement in public relations (PR). The results of a cross-sectional survey reveal two paths to the PR-journalism boundary crossing, although the level of boundary crossing is overall controllable. First, economic disruption indirectly predicts journalists' engagement in media pitching and media event planning through their identification with colleagues who have engaged in PR. Second, perceived waning social status both directly and indirectly predicts their engagement in media pitching and media catching, with their disidentification with PR practitioners as a mediator in the indirect relationship. These findings suggest that, while professional disruption may induce journalists to seek more information subsidy, their professional identity can be a source of both resistance against and support for this trend. Theories on social identity and intergroup relations are adopted to explain this dilemma.